Fuzzy system to evaluate performance and the physiological responses of piglets raised in the farrowing house with diﬀerent solar heating systems - Flavio Alves Damasceno; Carlos Eduardo Alves Oliveira; Jairo Alexander Osório Saraz; Lucas Hernrique Pedrozo Abreu; Patricia Ferreira Ponciano Ferraz (Revista Facultad Nacional de Agronomía Medellín, 2019)
The present work aims to develop a mathematical model, based on fuzzy set theory, for predicting performance and the physiological responses of piglets raised in the farrowing house with different solar heating systems. To do this, a solar heater prototype was constructed using alternative materials and the heating efficiency was compared with a commercial solar heater system. In order to thermally evaluate the heaters, temperature sensors were installed in the inlet and outlet pipes of each floor and thermal reservoir. The fuzzy system was developed and the variables dry air bulb temperature (Tbs) and relative humidity (RH) of the air were defined as inputs. Based on the input variables, the fuzzy system predicts the productive performance (weight gain - WG) and physiological responses (respiratory rate - RR, rectal temperature –RT, and skin temperature - ST) of piglets raised in an environment with solar heating. Based on the results, the fuzzy model was adequate for predicting the physiological responses and productive performance of piglets, presenting low standard deviation and high correlation with the validation data. This model can be used to assist producers in decision making, especially regarding maintaining animal welfare while the thermal environment changes.